Anti‐Cancer Effects of Nonequilibrium Atmospheric Pressure Plasma on Cancer‐Initiating Cells in Human Endometrioid Adenocarcinoma Cells. Issue 12 (24th November 2015) - Ikeda, Jun‐Ichiro; Tsuruta, Yoko; Nojima, Satoshi; Sakakita, Hajime; Hori, Masaru; Ikehara, Yuzuru
Abstract : To examine the effect of NEAPP on cancer‐initiating cells (CICs) that are believed to cause recurrence or metastasis due to their resistance to anti‐cancer drugs, the treatment of nonequilibrium atmospheric pressure plasma (NEAPP) combined with anti‐cancer drug cisplatin and NEAPP irradiation of tumor xenograft mice are performed in human uterine endometrioid adenocarcinoma cells. NEAPP treatment affects both ALDH‐low (non‐CICs) and ALDH‐high cells (CICs) more efficiently than cisplatin. In tumor xenograft mice, ALDH expression reduces in tumor with NEAPP irradiation. These results suggest that NEAPP treatment is effective not only on non‐CICs but also on CICs. Abstract : To cure cancers, it is necessary to control cancer‐initiating cells (CICs) that are believed to cause recurrence or metastasis. The treatment of nonequilibrium atmospheric pressure plasma (NEAPP) and NEAPP irradiation of tumor xenograft mice are performed in human uterine endometrioid adenocarcinoma cells. NEAPP treatment is effective not only on non‐CICs but also on CICs.